2002
DOI: 10.1017/s1138741600005795
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Family Factors Associated with Suicidal Ideation in Pre-Adolescents

Abstract: To assess the psychological and family factors associated with suicidal ideation in preadolescent children, we studied a sample of 361 students, average age 9 years old. Two groups were formed, on the basis of the presence (n = 34) or absence (n = 44) of suicidal ideation. Suicidal ideation was assessed with the Children's Depression Inventory and the Children's Depression Rating Scale-Revised. Depression, hopelessness, self-esteem, and perceived family environment were compared in both the suicidal ideation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…The issues assessed on subscale 'A' included frequent arguments among parents, criticizing and interfering attitudes of parents, disagreement between student and parent, poor trust, high expectations and lack of guidance. In earlier studies also, disturbed interpersonal relationship with parents was associated in 77% of adolescents with deliberate self-harm, [14,18] and higher stress in three quarters of suicidal adolescents. [17] In another study from Delhi, physical abuse and feeling neglected by parents were found to be signiÞ cant risk factors for suicidal behaviors.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The issues assessed on subscale 'A' included frequent arguments among parents, criticizing and interfering attitudes of parents, disagreement between student and parent, poor trust, high expectations and lack of guidance. In earlier studies also, disturbed interpersonal relationship with parents was associated in 77% of adolescents with deliberate self-harm, [14,18] and higher stress in three quarters of suicidal adolescents. [17] In another study from Delhi, physical abuse and feeling neglected by parents were found to be signiÞ cant risk factors for suicidal behaviors.…”
Section: Discussionmentioning
confidence: 80%
“…[18,21] In a large study from Guyana, 18.4% of students considered suicide in the last one year. [22] In another study from Nigeria, suicidal ideas were reported in 20% of the students, and suicidal attempt, in 12%.…”
Section: Students Stress and Suicidal Ideasmentioning
confidence: 99%
“…Suicidal behaviour is frequently associated with depression [1][2][3]. Descriptive epidemiology of children's and adolescents' suicidal behaviour shows, in a non-clinical sample of schoolchildren, self-reported suicidal ideation in approximately 1-14%, and depressive symptoms in 18-44% of cases [4][5][6][7]. The risk of developing suicidal behaviour is thought to be associated with cumulative exposure to a range of factors: social and family circumstances, personality, traumatic life experiences and mental health [3,[8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…While there have been reports on the prevalence and correlates of suicidal ideation in the developed world (Vinas et al, 2002;Joe et al, 2006), data from the developing world are limited. We therefore carried out this study to estimate the prevalence and assess socio-demographic correlates among in-school adolescents in Zambia.…”
Section: Introductionmentioning
confidence: 99%